(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The present study research the fixed points of meromorphic functions, and their higher order contrasts and moves, and sum up the instance of fixed points into the more broad case for first order distinction and move. Solidly, some appraisals on the order and the types of assembly of uncommon points of meromorphic functions and their disparities and movements are gotten.